2006
DOI: 10.1039/b511920k
|View full text |Cite
|
Sign up to set email alerts
|

MnO and NiO nanoparticles: synthesis and magnetic properties

Abstract: Nanoparticles of MnO with average diameters in the 6-14 nm range have been prepared by the decomposition of manganese cupferronate in the presence of TOPO, under solvothermal conditions. Nanoparticles of NiO with average diameters in the 3-24 nm range have been prepared by the decomposition of nickel cupferronate or acetate under solvothermal conditions. The nanoparticles have been characterized by X-ray diffraction and transmission electron microscopy. Both MnO and NiO nanoparticles exhibit supermagnetism, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
172
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(188 citation statements)
references
References 15 publications
16
172
0
Order By: Relevance
“…Assuming the cubic shape for nanoparticles, one can evaluate the change in the lattice volume being ∆V/V 0 ≃1% (V 0 =72.5 Å 3 for c-NiO and V=73.43 Å 3 for nanoNiO). Thus, our data confirm the expansion of the nano-NiO lattice, found recently by x-ray diffraction [10,11].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Assuming the cubic shape for nanoparticles, one can evaluate the change in the lattice volume being ∆V/V 0 ≃1% (V 0 =72.5 Å 3 for c-NiO and V=73.43 Å 3 for nanoNiO). Thus, our data confirm the expansion of the nano-NiO lattice, found recently by x-ray diffraction [10,11].…”
Section: Resultssupporting
confidence: 80%
“…We found that the lattice in nano-NiO expands compared to bulk nickel oxide (c-NiO), in agreement with other studies by EXAFS [28,34] and XRD [10,11]. The estimate, based on the EXAFS signal analysis from the first two-coordination shells (Table 1), suggests a volume expansion in nano-NiO by about 1%.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, the magnetic moment does not reach saturation even at the applied field of 50 kOe, and this is another indication of major AFM. In addition, noticeable hysteresis shift along the field direction was observed when measured at 5 K in ZFC condition, which is due to the interaction between major AFM and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 39 In dM/dH curve in as-synthesized NPs, a peak is observed at zero applied fields, which implies that there is a slope in dM/dH curve and this is a strong indication of the presence of FM component (inset, Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Therefore, other species of metal cations with similar size can occupy those defect sites. MnO nanoparticles have been synthesized by solvothermal decomposition of manganese cupferronate with a stainless autoclave at 325 °C in toluene, 39 or thermal decomposition of manganese acetate in the presence of triocylamine and oleic acid. 40 When the molar ratio between Fe(acac) 3 and Mn(acac) 2 is 1:1.7, plate-shape Mn x Fe 1-x O nanoparticles were obtained, which were identified in TEM (Figures 1a,1b,1d) and SEM ( Figure 2) images.…”
Section: Resultsmentioning
confidence: 99%